(untitled) (World Bulletin of Public Health, 2024)
This article provides a comprehensive overview of cognitive disorders observed in individuals experiencing post-COVID syndrome. It explores the current understanding of the neurological sequelae of COVID-19, focusing on neurocognitive impairments, and discusses potential mechanisms, risk factors, and management strategies